2022
DOI: 10.3389/fonc.2022.934008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the current molecular landscape and management of multiple myeloma patients with the t(11;14) translocation

Abstract: Multiple myeloma (MM) is a genetically complex disease. The key myeloma-initiating genetic events are hyperdiploidy and translocations involving the immunoglobulin heavy chain (IgH) enhancer on chromosome 14, which leads to the activation of oncogenes (e.g., CCND1, CCND3, MAF, and MMSET). The t(11;14) translocation is the most common in MM (15%–20%) and results in cyclin D1 (CCND1) upregulation, which leads to kinase activation and tumor cell proliferation. Notably, t(11;14) occurs at a higher rate in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
0
2
1
Order By: Relevance
“…Deletion 17p was also noted with a higher incidence in the sPCL (66%) and iCPC (50%) groups. In contrast to previously reported higher incidence of t(11;14) in up to 52% of pPCL patients, t(11;14) was only seen in 19% of our pPCL cohort [ 26 ]. Moreover, t(11;14) was also interestingly uncommon in Black patients in our cohort, presenting in 18% of the total Black cohort (n = 9), 15% pPCL, 24% sPCL, and 11% iCPC.…”
Section: Discussioncontrasting
confidence: 99%
“…Deletion 17p was also noted with a higher incidence in the sPCL (66%) and iCPC (50%) groups. In contrast to previously reported higher incidence of t(11;14) in up to 52% of pPCL patients, t(11;14) was only seen in 19% of our pPCL cohort [ 26 ]. Moreover, t(11;14) was also interestingly uncommon in Black patients in our cohort, presenting in 18% of the total Black cohort (n = 9), 15% pPCL, 24% sPCL, and 11% iCPC.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, it has been shown that the presence of numerous high-risk cytogenetic abnormalities in the same patient, such as multiple gains(1q)m del(1p)m del(IGH) and del(13q), has a greater impact on outcomes compared to a single high-risk aberration such as an isolated t(11;14) [43,44]. Therefore, we advocate for patients with t(11;14) and co-existing chromosomal abnormalities to be categorized as at least intermediate-risk than standard-risk [16,45].…”
Section: Dynamic Role Of T(11;14) In Shaping the MM Prognosis Landsca...mentioning
confidence: 99%
“…In addition to these agents, other small molecule targeted therapies have been developed to exploit specific characteristics of MM cells and pathways that are upregulated in cancer cells more broadly. These have included the histone deacetylase inhibitor panobinostat [21], the novel targeted cytotoxic drug–peptide conjugate melphalan flufenamide (‘melflufen’) targeting extramedullary disease in particular [22], and the selective inhibitor of BCL‐2 venetoclax, which is emerging as a biomarker‐directed therapy for patients with t(11;14) MM [23]. Having such options is valuable and important in the RRMM setting following prior mAb‐based and immunomodulatory drug‐based treatment and, increasingly, post CAR T‐cell or bispecific antibody therapy.…”
Section: Introductionmentioning
confidence: 99%
“…These have included the histone deacetylase inhibitor panobinostat [21], the novel targeted cytotoxic drug-peptide conjugate melphalan flufenamide ('melflufen') targeting extramedullary disease in particular [22], and the selective inhibitor of BCL-2 venetoclax, which is emerging as a biomarker-directed therapy for patients with t(11;14) MM [23].…”
mentioning
confidence: 99%